Increasing the relevance of records on motor development through specialized software - Tomescu, Gabriela; Stănescu, Monica-Iulia; Aivaz, Kamer-Ainur (Technium Social Sciences Journal, 2022)
Leisure motor activities are not a constant in the educational program of institutionalized children. In the context of several specialized studies suggesting that those who are raised in foster care have a slower or poorer physical development compared to those who grow up with their family, we have conducted a comparative study between a group of institutionalized children and a group of dancers, through which the level of motor development of the two categories could be established objectively. Given that dancesport is not yet used as a means of development and social integration for the children in orphanages, the purpose of this subject is to highlight the contribution of dancing to the psychomotor development of preadolescents. The results of the initial testing with the Optojump device indicate the effectiveness of dancesport in children from families. Thus, an intervention model was developed based on contents of dancesport, in order to stimulate the motor skills of institutionalized children. At the end of the research, significant differences were identified between the initial phase results and the final testing results.